EV+A 2000 : friends and neighbours. - Martinez, Rosa; Murray, Hugh; O'Reilly, Paul M.; Limerick City Gallery of Art; Exhibition of Visual + Art Limerick (Limerick : Limerick City Gallery of Art, 2001)
Friends and Neighbours explores the multiple possibilities of conviviality between artists of different generations, various countries and diverse aesthetic positions. Today as the hierarchies between the arts fade away, the notions of centre and periphery start to be put into question ; we can celebrate the resulting dispersion of artistic energies : there is not a single hegemonic trend that imposes its particular truth over the others ; multiple narratives are emerging and we are learning to respect the place of others while we try to create common areas of encounter. The best contemporary art seeks to construct dialogical relations with the viewers ; artists are not proposing eternal truths but rather ephemeral events, personal views, or process-centered experiences. This can be considered a weak response to the pervasive globalisation of transnational capitalism that imposes a single model of thought and consumerism. These paradoxes provoke in us both fascination and fear. In this context, to be friends or collaborative neighbours can help us face many of those contradictions, and awaken in us our capacity for critical thought.
Amer, Ghada ; Andrews, Colin ; Antoni, Janine ; Xu Bing ; Cotter, Bernadette ; Cunha, Alexandre da ; Derbyshire, Beth ; Doyle, Maria ; Guzman, Federico ; Hatoum, Mona ; Hausswolff, Carl Michael von ; Holten, Katie ; Keane, Alan ; Laherty, Bernie ; Leal, Ernesto ; McCarthy, Caroline ; McDonagh, Edwina ; Mackey, Christine ; Morgan, Deirdre ; Murray, Darren ; Murtezaoglu, Aydan ; Navridis, Nikos ; Neuenschwander, Rivane ; Nicholson, Veronica ; O'Neill, Fidelma ; Özseçen, Ebru ; Pogacar, Tadej ; Power, Deirdre A. ; Rist, Pipilotti ; Rogers, Ruth ; Sangar, Bülent ; Savage, James ; Seagrave, Anne ; Sierra, Santiago ; Smith, Bernard ; Taylor, Sean ; Teters, Charlene ; Vega, Sergio ; Zivic, Gregor
heel korte biog. per kunstenaar p. 20-176
Engels
EV+A 2000 : friends and neighbours, Limerick City Gallery of Art Limerick, 11 March -4 June 2000
boek